L'autonomia di apprendimento Atti della V giornata di studio sui materiali didattici per l'insegnamento delle lingue straniere - Scott Staton (Proceedings e report, 2010)
This book presents the most significant contributions of the fifth edition of the Study Days on didactic materials (foreign), held on 1st June 2007 at the University of Florence, and focused on the issue of "autonomous learning". The authors come from different institutional ambits and teach a variety of languages, while they share an interest in seeking modes and means for fostering the enhanced independence of the learner in identifying and attaining his or her individual objectives in the chosen language. The contributions range from aspects relating to the development of new styles of learning to those connected with technological innovation or the deficiencies of the same, leading to a meditation on the teacher/learner relationship in a variety of educational ambits.